La huerta: lugar biodiverso, desde donde se defiende la vida, Figueroa, Cauca - Maca Sanchez, Marlyn Patricia (2023)
The orchard is the place where a colossal diversity of food, medicinal plants, condiment, flowers, and wood are cultivated. Based on the orographic conditions, climates, and cultural dynamics of each region, related, farming knowledge is objectified. This paper analyzes the orchard territorial scale in Figueroa, Cauca, social scenario in which agricultural praxis is carried out, which articulates conservation and resistance practices, carried out day-to-day. The method of research is ethnographic, based on the role of ethnographer as assistant-companion in the orchard, and the use of techniques such as participant observation, direct interviews, and ethnographic interviews. Based on the field work, the orchard is identified as a biodiverse place, where there is a complex network of actions and thoughts, whose core axis is the defense of nature and territory, that is, life.